Incorporating Artificial Intelligence for Da’wah: Defining the State's Role - Dewi, Siti Malaiha; Hidayat, Mansur (JURNAL PENELITIAN, 2024)
This study aims to elucidate the role of the state as the primary actor in managing the extensive use of Artificial Intelligence (AI) in the realm of da’wah (calling others to practice the teachings of Islam), which has both positive and negative consequences. The identified negative impacts include the delegitimization of religious teachings and the authority of religious figures. This research utilizes a literature review approach, collecting and analyzing data from various sources such as books, websites, articles, and newspapers related to the application of AI in da’wah. The findings indicate that state intervention is crucial in regulating AI use through three main mechanisms: first, regulation; second, strengthening the roles of relevant actors; and third, supervision. Without proper regulation, the use of AI in da’wah can become unmanageable, leading to disinformation and the erosion of authoritative references. Therefore, this study underscores the importance of state involvement in ensuring that AI is employed ethically and effectively to support da’wah activities in Indonesia. These findings affirm that the state must actively regulate AI to maintain the integrity of religious teachings and the authority of religious figures, as well as to fully harness the positive potential of AI in the context of da’wah.